Electron-beam irradiation at low doses preserves dietary fiber content in Boletus edulis Bull.: Fr. wild mushroom - Fernandes, Ângela (2014)
Mushrooms are considered a good source of non-digestible carbohydrates, which represent a group of dietary fiber with various beneficial health effects to humans e.g., improve the function of the alimentary tract, helps lower postprandrial blood glucose, insuline and cholesterol, strengthens the immune system and antitumor activity [1]. Due to delicate nature, mushrooms suffer severe conservation problems and have to be processed to extend their short shelf-life. Drying is one of the most used processes for preserving mushrooms and, for decontamination, electron-beam irradiation also proved its technological feasibility to be safely used for reduce food losses [2]. In the present study, electron-beam irradiation (2, 6 and 10 kGy) was applied to dried samples of Boletus edulis Bull.: Fr. in order to evaluate the effects on fiber composition. The fruiting bodies were collected in Trás-os-Montes (Northeast of Portugal) in November 2012 and dried at 30 ºC in an oven. The irradiation was performed at the Institute of Nuclear Chemistry and Technology, in Warsaw, Poland. The determination of total available carbohydrate was carried out by the Anthrone method [3]. AOAC enzymatic-gravimetric methods, 993.19 and 991.42 were used for soluble and insoluble dietary fiber analysis [4]. B. edulis presented an important percentage of dietary fiber, soluble and insoluble in different ratios. The irradiated samples, especially for higher doses, gave some significant changes in total available carbohydrates and dietary fibers content; but, a lower dose (2 kGy) preserves carbohydrates, soluble and insoluble fiber content. Electron-beam irradiation at low doses is a feasible choice to extend mushrooms shelf-life and preserves the dietary fiber content.